2011
DOI: 10.4103/0973-6042.80466
|View full text |Cite
|
Sign up to set email alerts
|

The anterolateral approach to the proximal humerus for nonunions and delayed unions

Abstract: Nonunions of proximal humerus fractures can be disabling as a result of pain, deformity and instability, and are often found in geriatric patients with poor bone quality. There are relatively few studies examining the treatment of nonunions of the proximal third of the humerus and the ideal treatment and surgical approach remains unclear. This case series reports the successful use of the anterolateral acromial approach for treatment of the symptomatic proximal third humerus nonunions in a geriatric group of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Our study has a female-predominant population (M:F=2:4) like most of the studies, e.g. : Badman et al (0:18), Hettrich et al (0:3), Ahrens et al (1:4), Allende and Allende (0:7), Gao et al (2:5), Quadlbauer et al (3:6) [ 16 , 17 , 21 - 24 ].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Our study has a female-predominant population (M:F=2:4) like most of the studies, e.g. : Badman et al (0:18), Hettrich et al (0:3), Ahrens et al (1:4), Allende and Allende (0:7), Gao et al (2:5), Quadlbauer et al (3:6) [ 16 , 17 , 21 - 24 ].…”
Section: Discussionmentioning
confidence: 76%
“…Badman et al treated 18 patients with fibular allograft and the fixed-angle device showed union in 17 patients [ 16 ]. However, the ideal treatment for this disabling condition remains unclear and largely depends on the judicious use of treatment methods and surgical expertise [ 17 ]. We have noticed scalloping of the humeral head, bone gap, and local (or generalized) osteoporosis in all the cases, probably due to late presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other common treatments of intra-articular or distal humeral atrophic non-union include elbow arthrodesis, arthroplasty 16 , allografts 17e20 , open reduction and internal fixation 21 , prosthesis 22 or the Ilizarov technique 23 . From these options, we have chosen the posterior plate to reduce the distracting forces and used the opposing anterior bone splint to further increase stability at the fracture site 17e19, 24 . Besides stability, the osteo-inductive and osteo-formative abilities of the bone strut, bone chips and bone paste, provided a second mechanism to increase fracture healing and addition of mechanical load transfer 2,5,6,20,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The senior author favors the anterolateral approach for ORIF of proximal humerus fractures, both in the acute setting and in cases of nonunion [40]. The incision is centered between the anterior and middle heads of the deltoid, with the proximal extent of the incision approximately one finger breadth proximal to the anterolateral border of the acromion [39•].…”
Section: Authors Preferred Technique: Surgical Approachmentioning
confidence: 99%